The Influence of Nutritional Doses to the Character of Growth and Resultsof CerryTomatoes (Solanum pimpinellifolium) Subang Local Using Drip Irrigation System - Enceng Sobari (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2019)
Tomatoes are a type of horticultural plant that has an important role for national food. Tomato commodities are used as food ingredients and can be made various processed food industry products. Local cherry tomatoes are neglected and not yet widely used plants, but have the potential to be developed as a genetic resource in breeding programs in order to increase food diversification based on local resources because it is supported by huge market needs and low commodity availability of cherry tomatoes that is. An effective and efficient cultivation system is also an important factor in supporting the availability and quality of the products. The research aimed to knowing the local tomato cerry response Subang to the differentdoses of nutritional application administered through drip irrigation to affect the character of growth and results. The research method of the study uses the complete random plan (RAL) byusing 7 times with a 5-fold test and a follow-up test by using 5% Duncan assay.The results showed thattwo treatments (P2 and P3) application of nutrient doses were able to give a different response to all growth parameters while the parameters of the effect of nutrient application on local cherry tomatoes Subang has increased only in fruit diameter and thickness of fruit.